Age and compositional data of zircon from sepiolite drilling mud to identify contamination of ocean drilling samples. (27th August 2016) - Andrews, Graham D. M.; Schmitt, Axel K.; Busby, Cathy J.; Brown, Sarah R.; Blum, Peter; Harvey, Janet. C.
Abstract: Zircon extracted from drilled oceanic rocks is increasingly used to answer geologic questions related to igneous and sedimentary sequences. Recent zircon studies using samples obtained from marine drill cores revealed that drilling muds used in the coring process may contaminate the samples. The JOIDES Resolution Science Operator of the International Ocean Discovery Program has been using two types of clays, sepiolite and attapulgite, which both have salt water viscosifier properties able to create a gel‐like slurry that carries drill cuttings out of the holes several hundred meters deep. The dominantly used drilling mud is sepiolite originating from southwestern Nevada, USA. This sepiolite contains abundant zircon crystals with U‐Pb ages ranging from 1.89 to 2889 Ma and continental trace element, δ 18 O, and εHf isotopic compositions. A dominant population of 11–16 Ma zircons in sepiolite drilling mud makes identification of contamination in drilled Neogene successions particularly challenging. Interpretation of zircon analyses related to ocean drilling should be cautious of zircon ages in violation of independently constrained age models and that have age populations overlapping those in the sepiolite. Because individual geochronologic and geochemical characteristics lack absolute discriminatory power, it is recommended to comprehensively analyze all dated zircon crystals from cores exposed to drill mud for trace element, δ 18 O, and εHf isotopic compositions. Zircon analyzed in situ (i.e., in petrographic sections) are assumed to be trustworthy. Key Points: Abundant zircon in sepiolite drilling mud used in scientific drilling can contaminate rock samples Contaminating zircon grains may yield diverse and spurious ages and compositions